Dorsal hippocampal involvement in conditioned-response timing and maintenance of temporal information in the absence of the CS - Tam, Shu K.E.; Jennings, Dómhnall J.; Bonardi, Charlotte (Springer, 2013)
Involvement of the dorsal hippocampus (DHPC) in conditioned-response timing and maintaining temporal information across time gaps was examined in an appetitive Pavlovian conditioning task, in which rats with sham and DHPC lesions were first conditioned to a 15-s visual cue. After acquisition, the subjects received a series of non-reinforced test trials, on which the visual cue was extended (45 s) and gaps of different duration, 0.5, 2.5, and 7.5 s, interrupted the early portion of the cue. Dorsal hippocampal-lesioned subjects underestimated the target duration of 15 s and showed broader response distributions than the control subjects on the no-gap trials in the first few blocks of test, but the accuracy and precision of their timing reached the level of that of the control subjects by the last block. On the gap trials, the DHPC-lesioned subjects showed greater rightward shifts in response distributions than the control subjects. We discussed these lesion effects in terms of temporal versus non-temporal processing (response inhibition, generalisation decrement, and inhibitory conditioning).